Effects of Soy on Body Composition: A 12-Week Randomized Controlled Trial Among Iranian Elderly Women with Metabolic Syndrome - P Sajadi; Z Ahmad; A Rahmat; P Hanachi; Z Yassin; A Bakhtiari; S Shojaei (Tehran University of Medical Sciences, 2012)
Background: To examine the effects of soy [in the form of textured soy protein (TSP) and soy-nut] on body composition in elderly women with metabolic syndrome (MetS).Methods: A 12-week randomized clinical trial was conducted on 75 women between 60-70 years of age with MetS in rural health clinics around Babol, Iran in 2009. The participants were randomly assigned to one of the three groups of soy-nut (35g/d), TSP (35g/d) and control. Body fat, lean mass and anthropometric indicators were measured before and after intervention, too.Results: Participants were classified as overweight and showing android fat distribution. After 12 weeks of intervention, both soy-nut and TSP groups showed an increase of non-significant in lean mass (0.9 and 0.7 kg), hip circumference (0.45 and 0.28 cm), triceps skinfold (TSF) thickness (0.87 and 0.67mm) and reduction in BMI (-0.15 and -0.33), waist circumference (-0.83 and -1.2) and body fat (-1.5% and -1.7%). Significant increase in the mean change of TSF and lean mass was observed in the users of soy-nut compared to the control group (P<0.01, P<0.05).  Conclusion: 12-week intervention of soy had a mild favorable effect on body composition in elderly women with MetS.